Digital literacy and chemistry proficiency among first-year university students in Eastern Cape, South Africa - Dyantyi-Gwanya, Noluntu; Mavenge, Lusanda; Ncanywa, Thobeka; Asaleye, Abiola John (Frontiers in Education, 2025)
IntroductionThe low proficiency in chemistry by first-year students in South Africa impairs their capacity to grasp and apply crucial concepts, leading to high failure and dropout rates. This study investigates the effects of digital literacy on first-year entering students chemistry content proficiency in one South African university in the Eastern Cape.MethodThe study employed an interpretivist paradigm and a qualitative methodology in the form of open-ended questionnaires to elicit detailed insights from both students and lecturers. The purposively selected sample comprises 10 participants, including eight students and two lecturers. Constructivist Learning Theory and Technology Acceptance Model underpinned the study, while thematic analysis was used for data analysis.ResultData analysis reveals significant challenges in digital literacy, especially among students from rural areas with little prior exposure to digital technologies. The findings emphasize the importance of digital tools such as molecular visualization software and interactive simulations in improving students' chemistry comprehension and performance. The study emphasizes the ongoing digital divide, which impedes the effective use of these technologies.DiscussionIt concludes that bridging this gap necessitates comprehensive support systems, such as developing user-friendly digital platforms and ongoing professional development for lecturers to ensure they are adequately equipped to guide students.